Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2012)
Commitments under new PRGT-supported programs are expected to increase in 2012 in part reflecting the weaker global economic outlook. PRGT commitments in 2011 amounted to SDR 1.2 billion, unchanged from their 2010 level. Staff projections suggest demand could rise to about SDR 2 billion in 2012. If all elements of the 2009 financing package are secured, the PRGT will have an annual average lending capacity of SDR 2.2 billion over 2012-14, or SDR 1.6 billion through 2015. Additional pledges of SDR 1 billion in loan resources are still required to secure the targeted loan resources approved under the 2009 financing package. Fourteen members have so far pledged SDR 9.8 billion in new loan resources for the PRGT compared with the target of SDR 10.8 billion. New borrowing agreements totaling SDR 9.5 billion have been signed with thirteen lenders.